ESTUDIO DE LA INFLUENCIA DE LAS HARINAS DE Cicer arietinum (Garbanzo) Y Glycine max (Soja) EN LAS CARACTERÍSTICAS FISICOQUÍMICAS Y ORGANOLÉPTICAS DE UN PRODUCTO CÁRNICO (Tipo hamburguesa) DE Arapaima gigas (Paiche) - Ponce Arévalo, Lady Diana (2023)
The objective of the project is to study the influence of Cicer Arietinum (chickpea) and Glycine max (soybean) flour on the physicochemical and organoleptic characteristics of a meat product (hamburger type) of Arapaima Gigas (paiche) using cuts such as (loin, belly and whole) for the formulation. The development of the research was carried out by elaborating the product and then proceeding to incorporate the flours to proceed with the analysis and acceptance. To determine the differences between the physicochemical properties, an AxB design with 3 replications was used as the study factors (Factor A: Types of cuts, Factor B: Types of flours). To establish the effects between the levels of the treatments, Tukey's significance test was applied (p<0.05). The results of the data obtained were analyzed by means of the statistical packages "STATGRAPHICS" and "STATISTICA". Regarding the types of cuts, it was observed that the belly presented the best physicochemical characteristics, as well as protein, pH and humidity, while the influence of chickpea flour presented the best results. As for the acceptability of the paiche hamburger, the best results were obtained when chickpea flour was applied, using the loin cut type.